CRITICAL DISCOURSE ANALYSIS OF SHERLY TJOANDA'S POLITICAL IMAGE AS A WOMAN IN THE ROSI KOMPAS TV PROGRAM "NORTH MALUKU GOVERNOR SHERLY TJOANDA SPEAKS CANDIDLY ABOUT THE MINING ISSUE" - Laura Septa Amelia Elrista Pohan; Heidy Arviani (INJOSEDU: International Journal of Social and Education, 2026)
The study entitled Critical Discourse Analysis of Sherly Tjoanda's Political Image as a Woman in the Rosi Kompas TV Program "North Maluku Governor Sherly Tjoanda Speaks Candidly About the Mining Issue" is motivated by the importance of understanding how women's political image is constructed amid the influence of gender ideologies, particularly patriarchy and persistent gender stereotypes in society. This study addresses the question of how Sherly Tjoanda's political image is constructed through the discourse presented in the program. Accordingly, it aims to analyze the construction of women's political image through the dimensions of text, social cognition, and social context. This research employed a qualitative approach using Teun A. van Dijk's Critical Discourse Analysis (CDA) framework. Data were analyzed through three stages: description, analysis, and interpretation of textual structures, social cognition, and social context. The theoretical framework integrates Critical Discourse Analysis, political image theory, and the concept of gender ideology in politics. The findings reveal that Sherly Tjoanda's political image is constructed through communication strategies emphasizing competence, decisiveness, and responsiveness in addressing public issues while simultaneously negotiating her identity as a female political leader. The study concludes that women's political image is a discursively constructed phenomenon shaped by language, media representation, and broader social structures. Therefore, effective political communication strategies are essential for establishing political legitimacy while challenging and negotiating prevailing gender stereotypes.